2010
DOI: 10.1111/j.1526-100x.2010.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fruit Essential Oils to Assist Forest Regeneration by Bats

Abstract: Frugivorous bats can be attracted with essential oils from ripe chiropterochoric fruit. We evaluated the efficiency of these oils to attract bats in degraded areas within the Atlantic Rain Forest, particularly pasture and agricultural land. We hypothesized that induction units (IUs), each containing a rubber septum impregnated with oil, would have more bat activity than their respective control units (CUs; without the oil). To test this hypothesis we monitored bat flight activity with night-vision infrared vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 37 publications
1
27
0
2
Order By: Relevance
“…Frugivorous bats are fundamental for the maintenance of biodiversity and environmental services, such as seed dispersal in Neotropical ecosystems (Bianconi et al, 2012). Based on a detailed knowledge of bat fruit interactions, substances from vegetable origin (fruits, essential oils, and floral compounds) have become a useful attractant for frugivorous bats, increasing the potential for restoration projects (Bianconi et al, 2012;Parolin et al, 2015). Our results corroborated these assumptions as all studies with frugivorous bats showed attraction for at least one substance of vegetable origin used.…”
Section: Type Of Substances Used and Interactions With Mammalssupporting
confidence: 82%
See 1 more Smart Citation
“…Frugivorous bats are fundamental for the maintenance of biodiversity and environmental services, such as seed dispersal in Neotropical ecosystems (Bianconi et al, 2012). Based on a detailed knowledge of bat fruit interactions, substances from vegetable origin (fruits, essential oils, and floral compounds) have become a useful attractant for frugivorous bats, increasing the potential for restoration projects (Bianconi et al, 2012;Parolin et al, 2015). Our results corroborated these assumptions as all studies with frugivorous bats showed attraction for at least one substance of vegetable origin used.…”
Section: Type Of Substances Used and Interactions With Mammalssupporting
confidence: 82%
“…The use of some substances is already well established for some mammal groups. For example, frugivorous bats are usually attracted by substances from vegetable origin such as floral compounds and essential oils (Bianconi et al, 2012;Parolin, Mikich, & Bianconi, 2015;von Helversen et al, 2000). However, the majority of substances used for specific groups and species lack replications and specific tests, are restricted to a limited number of species, and do not make use of controls (Acosta-Jamett & Simonetti, 2004;Lucherini et al, 2009;Portella, Bilski, Passos, & Pie, 2013;Trolle, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have tested novel, bat-attraction techniques, primarily focused on odiferous fruit oils (Bianconi et al 2007(Bianconi et al , 2012 and artificial tree cavity roosts (Kelm et al 2008;Reid et al 2013). Yet neither of these methods has demonstrably accelerated forest succession (Reid & Holl 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[18], [19], [32][35]). The importance of vertebrate seed dispersal has been recognized by the implementation of restoration techniques which encourage dispersal, such as the planting of fruiting trees and ‘tree islands’ within degraded areas [36][38].…”
Section: Introductionmentioning
confidence: 99%